Prevalence and genetic diversity of haematozoa in South American waterfowl and evidence for intercontinental redistribution of parasites by migratory birds. Issue 1 (April 2015) - Smith, Matthew M.; Ramey, Andrew M.
Graphical Abstract: Highlights: Detected an overall apparent prevalence rate of 3.1% for haematozoa parasites. Twelve unique haematozoa haplotypes identified. Evidence for intercontinental exchange of hematozoa lineages by migratory birds. Evidence of host-specificity for Haemoproteus and Leucocytozoon parasites. Abstract: To understand the role of migratory birds in the movement and transmission of haematozoa within and between continental regions, we examined 804 blood samples collected from eleven endemic species of South American waterfowl in Peru and Argentina for infection by Haemoproteus, Plasmodium, and/or Leucocytozoon blood parasites. Infections were detected in 25 individuals of six species for an overall apparent prevalence rate of 3.1%. Analysis of haematozoa mitochondrial DNA revealed twelve distinct parasite haplotypes infecting South American waterfowl, four of which were identical to lineages previously observed infecting ducks and swans sampled in North America. Analysis of parasite mitochondrial DNA sequences revealed close phylogenetic relationships between lineages originating from waterfowl samples regardless of continental affiliation. In contrast, more distant phylogenetic relationships were observed between parasite lineages from waterfowl and passerines sampled in South America for Haemoproteus and Leucocytozoon, suggesting some level of host specificity for parasites of these genera. The detection of identical parasite lineages in endemic, South American waterfowl and North American ducks and swans, paired with the close phylogenetic relationships of haematozoa infecting waterfowl on both continents, provides evidence for parasite redistribution between these regions by migratory birds.